Geomorphology of the Piramagroon–Kanikhan Valley, Sulaimani Governorate, Kurdistan Region, North Iraq - Ahmad, Kamal Haji Karim; Bety, Azhar; Khanaqa, Polla Azad (International Journal of Geography and Geology, 2015)
Piramagroon-Kani Khan (PK) valley runs parallel to Pira Magrun and Surdash anticlines almost in NW- SE trend and merges with the Lesser Zab River 9 kms southeast of Dokan town. The valley runs within the soft rocks of Shiranish, Tanjero and Kolosh formations. The valley bottom is gently sloping plain which divided longitudinally by Charmaga stream into two asymmetrical parts (northeast and southwest parts). The northeast part is wider than the other one mostly covered by Recent and Pleistocene coarse alluvium with a thickness of 1-20meters. The southwestern part is relatively narrow and mainly covered by slide debris and dislocated blocks of Sinjar Formation. Northern eastern side is formed by differential erosion and its slope is the dip slope since it nearly coincides with the dip of the strata of the Kometan and Qamchuqa Formations. The southwestern side is scarp slope which has lesser elevation and formed mainly by sliding processes and manly covered by slide debris. The surface of this part has hilly and hummocky topography. The alluviums are belonging to debris flow and river bed deposits. According to age of deposition, the alluvium is grouped in two types which are Holocene (Recent) and Pleistocene types. The first type has mainly caliber of gravels and sand which deposited on the valley bottom plains and suitable for cultivating. The second type has coarser grain sizes which consist of a mixture of blocks, boulder and graves. This type exists either on the hills or it form as isolated plateaus that about 30 high from the surrounding. Now, only as a small or large pachy remnant on the top of ridges and hills or exist as small plateaus which are transformed these elevated lands due to inversion of topography by erosion and weathering.